Decoding the IT value problem : an executive guide for achieving optimal ROI on critical IT investments - Fell, Gregory J., 1964- (Wiley CIO serie, 2013)
"Gain greater returns from your IT investmentsRevealing the secrets to proven, effective strategies that enable businesses to leverage the full value of highly expensive IT investments, Decoding the IT Value Problem is a no-nonsense guide for making smart IT investments and cutting through the noise of vendor marketing and media hype. Author Gregory Fell describes in rich detail the actual processes, frameworks, infrastructure and discipline required to develop and execute corporate IT strategies that areprofitable and sustainable. Provides a proven framework for developing and successfully executing profitable IT strategies Plain English guidance for gaining the most return on investment from critical IT investments Explores developing and executing IT strategy; forecasting, calculating and managing IT costs; leveraging IT investments to drive business growth; IT and the evolving global economy; IT value management; communicating IT value across the enterprise; and leading change, transformation and innovation If you're a senior level manager or executive responsible for managing IT value in your business, Decoding the IT Value Problem is the practical and clearly written guide you'll turn to, with tools and tips for smart investment and management of IT costs"--